(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article analyzes the causes of family disputes and divorces, statistics on divorces in the country, various statistics on disability, the role of children with disabilities in family relationships and the results of public opinion polls, referral of children with disabilities to society.